Evaluation of mir-146a and mir-155 plasma expression levels in patients with mycosis fungoides and detection of single nucleotide polymorphisms in their sequence. (October 2021) - Avgeros, Chrysostomos; Patsatsi, Aikaterini; Dimitriadis, Dimitrios; Koletsa, Triantafyllia; Papathemeli, Despoina; Ziampa, Kyriaki; Avgerou, Paraskevi; Lazaridou, Elizabeth; Hytiroglou, Prodromos; Tzimagiorgis, Georgios; Georgiou, Elisavet
Abstract : Introduction: Mycosis fungoides (MF), the most common form of cutaneous T-cell lymphomas presents with a broad spectrum of clinical and histopathologic manifestations. Diagnosis is often delayed, especially at the early stages. Clinicopathologic correlation and integration of molecular data is essential for a timely diagnosis and treatment. The use of microRNAs as biomarkers in biopsies and/or biological fluids has gained great interest over the last years. The aim of the present study was to analyze the expression levels of microRNAs (mir)-146a and -155 in the plasma of MF patients and healthy volunteers and to detect the presence of single nucleotide polymorphisms (SNPs) in their genes. Patients and methods: The appropriate sample size for statistical power equal to 0.94 (1–β=94%) and significance level at 0.05 (α=5%) was determined by a pilot study, using G.Power 3.1.9.2. The optimal sample size was calculated at n=82, with a ratio of MF patients/healthy individuals equal to 1:1. All samples were derived from consenting individuals. The mirs' plasma expression was evaluated with real-time quantitative reverse transcription PCR, and the relative quantity was calculated by the 2 –ΔCt method using cel-mir-39 as reference gene. In a subset of patients, the promoter region and/or the pre-microRNA genomic region of these mirs were scanned for the presence of SNPs in DNA extracted from white blood cells, by Sanger sequencing. Statistical analysis was performed with the statistical package IBM SPSS 25. Results: Plasma levels of mir-146a and mir-155 were significantly higher in patients with MF as compared to healthy volunteers (p=0.001 and p=0.028 respectively). Moreover, plasma levels were higher in patients with early MF vs healthy individuals (p=0.001 and p<0.001, for mir-146a and -155, respectively). Patients with advanced MF demonstrated higher expression levels of mir-146a and -155, when compared to early MF patients (p=0.009 and p=0.002). A positive correlation was detected between plasma levels of the two mirs in patients' samples (p<0.001). No correlation was detected between the expression of either mir and age/gender of the patients. The genotypes' frequencies for rs2910164 (CC/CG/GG) were 0.05/0.45/0.55 for MF patients and 0.1/0.54/0.36 for controls. The genotypes' frequencies for rs767649 (TT/AT/AA) were 0.76/0.18/0.06 for MF patients and 0.9/0.1/0 for controls. There was no significand difference in the genotype patterns between patients and controls for either SNP. No SNPs were detected in the pre-mir-155 sequence. Discussion: The presence of SNPs regulating mirs' function may need to be evaluated in larger cohorts, while the detection of increased mir-146a and mir-155 plasma levels in MF patients is an important finding in the attempt to establish putative non-invasive biomarkers for prompt diagnosis, prognosis, and adequate therapy of these patients.